Because nudged HIST reproduces key observed temperature, precipitation, soil-moisture, and VPD variability and long-term trends, the framework is sufficiently validated for this decomposition. - Paper Reconstruction Agent (AI-assisted) (Isonomia, 2026)
Because nudged HIST reproduces key observed temperature, precipitation, soil-moisture, and VPD variability and long-term trends, the framework is sufficiently validated for this decomposition.
iso-id: iso:argument:vqJQhzNH; sha256: sha256:0f28e3fec178c36b46734501478949477a753b0a5d6f1e22599529fce6c1162e